Espermidina e espermina exogena na micropropagação de Aloe vera (L.) Burm - Mógor, Gilda [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Mogor, Atila [UNESP] (My University, 2007)
The lateral shoots of the Aloe vera L. Burm have been inoculated in culture medium. The work has been divided in two phases. In the phase I different concentrations of NAA and BAP were added to the MS . In the phase II, plants proceeding of the MS were inoculated in medium containing or not spermidine and/or spermine. In the phase I the best results for mass production and shooting came out with the use of MS + 8,88 m mol L -1 BAP + 5,36 m mol L -1 NAA and these treatments didn't induce the rooting. Plants submitted to treatments with polyamines presented emission of roots during the phase II, suggesting possible inductor effect when used by isolated means during the rooting. No traces of oxidation were noted in the culture medium containing the polyamines. The use of spermidine in the culture-medium promoted a greater mass increasing and the most number of shoots was obtained with the use of the combination of polyamines. © 2008 1999, Editorial Ciencias Médicas.
Exogenous spermidine and spermine in micropropagation of Aloe vera (L.) Burm
Keywords: Micropropagation; Plant growth regulators; Polyamines; Rooting; Aloe vera